Financial liberalization, multinational banks and credit supply: The case of Poland - Christian E. Weller (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
Part of the Polish transformation process has been an opening of the domestic financial market to foreign entrants. While the number of MNBs rises from zero to fifteen within six years, the ratio of bank credit to private and public enterprises relative to GDP decreases continuously after 1991. In this paper, I develop an argument as to why these two trends may be connected. Further, using monthly data provided by the weekly Polish publication Gazeta Bankowa, by the National Bank of Poland, the Central Statistical Office, the BIS, and the IMF, I test the hypothesis that more MNB entry may lead to a declining credit supply during the early stages of the transition process. Multivariate regression results indicate that more MNB entry results in a lower credit supply by Polish banks during the early transition phase. This result holds regardless of the measurement of international financial competition, and regardless of a bank's history, and it is only partially affected by a bank's location. More importantly, the overall impact of increased international financial competition on the credit supply of Polish banks is strong enough to lower the total credit supply in the Polish economy. Since an earlier study has found that Polish industries operate under hard budget constraints and are finance constrained during the early stages of the transition process, a reduction in the credit supply has adverse effects on business investments (Cornelli, Portes, and Schaffer, 1996; Weller, 1999).
Keywords: F36; O52; P23; P33; P34; 330; Multinational banks; credit supply; financial liberalization; transition economy; Poland; Kapitalmarktliberalisierung; Internationale Bank; Kreditmarkt; Internationaler Wettbewerb; Kreditrationierung